Hepatic pseudocyst as a result of ventriculoperitoneal shunts: Case report and review of the literature - Kaplan, Metin; Ozel, S. Kerem; Akgun, Bekir; Kazez, Ahmet; Kaplan, Serpil (Karger, 2007)
Hepatic pseudocyst formation is a rare intra-abdominal complication of ventriculoperitoneal shunts. The presence of an intracranial tumor and a history of central nervous system infection are major risk factors for the development of this complication. Hepatic pseudocysts secondary to ventriculoperitoneal shunts can be classified as intra-and extraaxially growing cysts. On abdominal computed tomography images, extra-axially growing pseudocysts are typically surrounded by a fine annulus that shows continuity to hepatic parenchyma. For treatment of extra-axially growing hepatic pseudocysts, surgical unroofing of the cyst and repositioning of the catheter is an effective method if there is no shunt infection and/or dysfunction.
Keywords: ventriculoperitoneal shunt complication; hepatic pseudocyst; medulloblastoma